1988
DOI: 10.1130/0091-7613(1988)016<0422:pafbra>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Paleomagnetic arguments for block rotations along the Arakapas fault (Cyprus)

Abstract: Paleomagnetic data from the sheeted dike complex north of the Arakapas fault reveal significant internal rotations. The north-south-trending dikes have remanent magnetization directions close to the well-known westerly paleomagnetic direction of the Troodos massif, whereas the east-west-trending dikes near the Arakapas fault have northerly remanent magnetization directions. The paleomagnetic data are in agreement with the apparent clockwise rotation of the dikes. Contrary to recent geological analyses which po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0

Year Published

1989
1989
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 19 publications
0
47
0
Order By: Relevance
“…The location of the Solea graben was originally constrained by the orientation of normal faults, opposing tilt of sheeted dikes, and rotated blocks of lava flow [Hurst et al, 1994]. Paleomagnetic study of the gabbroic suite [Granot et al, 2006] confirmed the location of the suspected paleospreading Solea axis and showed a clockwise rotation of remanence directions in the inside corner north of the Arakapas Transform fault ( Figure S1 in the auxiliary material), similar to the rotations shown for the overlying sheeted dikes [Allerton, 1989;Bonhommet et al, 1988], pillow lavas and hydrothermal sediments (umbers) [Morris et al, 1990]. …”
Section: Tectonic Settingmentioning
confidence: 65%
See 1 more Smart Citation
“…The location of the Solea graben was originally constrained by the orientation of normal faults, opposing tilt of sheeted dikes, and rotated blocks of lava flow [Hurst et al, 1994]. Paleomagnetic study of the gabbroic suite [Granot et al, 2006] confirmed the location of the suspected paleospreading Solea axis and showed a clockwise rotation of remanence directions in the inside corner north of the Arakapas Transform fault ( Figure S1 in the auxiliary material), similar to the rotations shown for the overlying sheeted dikes [Allerton, 1989;Bonhommet et al, 1988], pillow lavas and hydrothermal sediments (umbers) [Morris et al, 1990]. …”
Section: Tectonic Settingmentioning
confidence: 65%
“…Paleomagnetic studies of the upper crust and overlying sedimentary sequence [e.g., Morris et al, 2006] showed that the entire ophiolite had rotated by nearly 90°anti-clockwise during the emplacement (late Cretaceous to early Eocene), leading to an expected remanent magnetization direction of 273°/38°(a 95 = 6.5°). Any deviation of remanent magnetization from this direction reflects pre-emplacement accretion-related rotations [e.g., Allerton and Vine, 1987;Bonhommet et al, 1988;Ebert et al, 2010;MacLeod et al, 1990]. Although the gabbros studied here lack independent structural information, remanence directions together with the assumed N-S trend of rotation axis (parallels the Solea axis) are sufficient to correct for tectonic rotations.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the sheeted dikes show 60-80° rotation at the same sense (Fig. 4b) [20,22]. This means that in the IC terrain the lower crust deforms at the same sense as the upper crust, but the amount of rotation is smaller.…”
Section: Inside Cornermentioning
confidence: 86%
“…Maximum deformation, with ~90° cumulative clockwise rotation, is evident close to the transform (i.e., sheeted dike trending E-W). The degree of rotation gradually declines with increasing distance from the Arakapas transform reaching zero 6 km to the north [20][21][22][23].…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation